Fine Pore Structure Characterization in Two Gessoes Using Focused Ion Bean Scanning. Issue 1656 (22nd August 2014) - Doutre, Michael; Freeman, Ashley; Diak, Brad; Murray, Alison; Bevan, George; Fuster-López, Laura
ABSTRACT: The movement of fluids through a porous medium is a function of the material type and the size and morphology of the voids. In the conservation of painted artworks, the movement of materials (for example, cleaning solutions) is a major factor in how a work reacts to treatments and a large influence on how the work will change with time. Of particular importance in the conservation of painted surfaces is the preparatory layer. This is a highly active transport medium because it is generally highly porous and a comparatively large and uniform component of a painted surface. In this work, a gesso film of calcium carbonate and rabbit skin glue, typical of the preparatory layer of many painted works, and an acrylic-based gesso film were imaged by focused ion beam (FIB) scanning. The gessoes were milled and scanned with gallium ions serially, in sequential planes orthogonal to the plane of the film. This yielded quantifiable measurements of the fine internal structures at a resolution far higher than previously reported for this type of material. This enabled a greater understanding of the geometry of the internal surfaces, increasing the understanding of the mechanics of capillary flow and diffusive behavior in this extremely common and significant material.